The Role of the Department of Manpower in Protecting Former Indonesian Migrant Workers: Normative Analysis and Implementation Challenges - Endang Yulianingsih; Sri Astutik; Noenik Soekorini (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyse the role of the Department of Manpower in providing protection to former Indonesian Migrant Workers (PMI) returning from abroad and to identify the challenges encountered in performing this function. This research employs a normative juridical approach using secondary data sources, including statutory regulations, scientific journals, and institutional reports from 2020 to 2025. The findings reveal that the Department of Manpower plays several key roles, including providing information and education, coordinating with related agencies, offering legal assistance, supporting social and economic reintegration, and monitoring non-procedural placements. These roles are firmly grounded in Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers and Government Regulation Number 59 of 2021. However, implementation remains constrained by inaccurate data, limited human resources and budget, weak institutional coordination, and suboptimal legal complaint services. Despite these challenges, efforts have been made through strengthening integrated services, staff training, public education, and the use of information technology. This study concludes that the protection of former migrant workers requires a holistic, participatory, and sustainable approach to ensure the fulfilment of their rights as mandated by law.